Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada CV Ozzie Motor Kota Bandung - Reza Satya Yudha Perwira; Dahlan Ramdhani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research is motivated by the existence of several phenomena related to less than optimal employee performance at CV Ozzie Motor Bandung City. The aim of this research is to find out how much influence workload and work environment have on the performance of CV Ozzie Motor employees. The method used is descriptive and associative methods. The unit of analysis is 40 employees who work at CV Ozzie Motor, Bandung City. The research instrument is a questionnaire. The sampling technique uses samples without probability or saturated samples. The analysis method uses multiple linear regression and validity and reliability testing. The research results show that partially the workload variable (X1) has no effect on the performance variable (Y), while the work environment variable (X2) has a positive and significant effect on the performance variable (Y). Simultaneously, workload (X1) and work environment (X2) influence performance (Y) by 22.9%, while the remaining 77.1% is the influence of other variables not studied.